Do Religious/Spiritual Resources Moderate the Association Between Suffering and Religious/Spiritual Struggles? A Three‐Wave Longitudinal Study of US Adults with Chronic Illness. Issue 3 (13th November 2022) - Kent, Blake Victor; Cowden, Richard G.; Counted, Victor; Davis, Edward B.; Rueger, Sandra Y.; Worthington, Everett L.
Abstract: In this prospective study of US adults with chronic illness (n = 302), we examined the associations of subjective suffering and religious/spiritual (R/S) resources (i.e., religious coping, religious commitment, and spiritual fortitude) with the subsequent experience of R/S struggles. Using a rigorous analytic approach that involved adjusting for numerous covariates and prior values of all exposures and the outcome assessed in Wave 1, we found that suffering assessed in Wave 2 was associated with an increase in subsequent R/S struggles assessed 3 months later (Wave 3). There was modest evidence suggesting that religious commitment and spiritual fortitude (but not religious coping) moderated the association between suffering and subsequent R/S struggles, such that there was a stronger positive association between suffering and R/S struggles at higher levels of each moderator. This study provides preliminary evidence that R/S struggles may be commonly experienced by those with high religious engagement in the face of suffering.